Faktor-Faktor yang Berhubungan dengan Perilaku Higiene Penjamah Makanan di Kantin Sekolah Dasar Kecamatan Telanaipura Kota Jambi Tahun 2025 - Cici Permata; Willia Novita Eka Rini; Andree Aulia Rahmat; Hendra Dhermawan Sitanggang (Pusat riset dan Inovasi Nasional, 2026)
Food safety is a crucial aspect of public health, particularly for elementary school children who frequently consume street food or snacks sold within school environments. Food handlers play a key role in determining the level of hygiene and sanitation of the food served. This study aims to analyze the factors associated with food handlers’ hygiene behavior in elementary school canteens in Telanaipura District, Jambi City. This research employed a quantitative method with a cross-sectional approach involving 41 food handlers as respondents. Data were collected through structured interviews using questionnaires and direct observations based on hygiene and food sanitation standards in accordance with the Regulation of the Minister of Health No. 1096/Menkes/PER/VI/2011. Data were analyzed using univariate and bivariate methods with the Chi-Square test at a significance level of p < 0.05. The results showed that most food handlers exhibited poor hygiene behavior (61.0%). There were significant relationships between knowledge (p = 0.048), attitude (p = 0.000), and availability of facilities and infrastructure (p = 0.000) with hygiene behavior, while education level showed no significant association (p = 0.187). It can be concluded that improving hygiene behavior requires continuous training, supervision, and provision of adequate sanitation facilities to support food safety in school environments.